An assessment of product performance analysis on the overall cooperate performance : a case of Delta Cooperation Limited - Mahanzu, Michael (Midlands State University, 2020)
The motive of the study was to assess the extent of product performance analysis’s impact on the overall corporate performance of Delta Corporation. The research’s statement of the problem exposed that the decrease in revenue over the past 3 years and growing production costs resulting in poor performance of the corporation is a cause for concern. This prompted for the research in which the study endeavours on how best product performance can be improved at Delta Corporation. Literature view was undertaken in an attempt to disclose what other world acclaimed authors had to say concerning product performance analysis. Internet journals proved to be the source of literature review. Descriptive research design was used in this research with both the use of structured questionnaires and interviews due to its economic effectiveness. Research instruments, sources of data, samples and population were issued in this particular research. Pie charts and tables was used to demonstrate research findings and responses from primary data. Research findings reflect that ABC costing, regulatory pricing, effective distribution channels and quick adaptability to change surely enhance product performance in Delta Corporation. The researcher offered the recommendations that the corporation should adhere to the best practises emphasised in this research such as employee participation in policy formulation.